Peripheral calcifying odontogenic cyst: a case report and comprehensive review of 60 years of literature - Sheng, Sally; Tipton, Nicholas; Chang, Jennifer; Meng, Hsiu-Wan; Tribble, Gena D. (Frontiers in Oral Health, 2023)
Peripheral Calcifying Odontogenic Cyst (PCOC) is the extraosseous form of calcifying odontogenic cyst that is limited to peripheral soft tissue without bony involvement. This case report presents a case of PCOC manifested as a progressive growth of gingival mass in a young male treated with excisional biopsy. Histological examination confirmed diagnosis of PCOC with presence of characteristic ghost cells and sporadic calcifications. No recurrence of the lesion and no complication were noted at three-year follow-up. Review of available literature on PCOC noted a predilection of occurrence in the mandible (61%) and in the anterior area of the jaws (58%). Mean age of patients was 41.7±SD25.43(7-83) and 95% CI [33.6, 49.8] yrs. Mean size of the lesions was 1.38±SD1.1(0.5-4.3) and 95% CI [0.93, 1.83] cm. Gender distribution was noted to be 51.3% male and 48.7% female.